Silicon Nitride for High-Temperature Applications - Klemm, Hagen (Journal of the American Ceramic Society, 2010)
In this paper, a summary of the development of high‐temperature silicon nitride (T>1200°C) is provided. The high‐temperature capacity of various advanced commercial silicon nitrides and materials under development was analyzed in comparison with a silicon nitride without sintering additives produced by hot isostatic pressing. Based on this model Si3N4 composed of only crystalline Si3N4 grains and amorphous silica in the grain boundaries the influence of various sintering additive systems will be evaluated with focus on the high‐temperature potential of the resulting materials. The specific design of the amorphous grain‐boundary films is the key factor determining the properties at elevated temperatures. Advanced Si3N4 with Lu2O3 or Sc2O3 as sintering additive are characterized by a superior elevated temperature resistance caused by effective crystallization of the grain‐boundary phase. Nearly clean amorphous films between the Si3N4 grains comparable to that of Si3N4 without sintering additives were found to be the reason of this behavior. Benefit in the long‐term stability of Si3N4 at elevated temperatures was observed in composites with SiC and MoSi2 caused by a modified oxidation mechanism. The insufficient corrosion stability in hot gas environments at elevated temperatures was found to be the main problem of Si3N4 for application in advanced gas turbines. Progress has been achieved in the development of potential material systems for environmental barrier coatings (EBC) for Si3N4; however, the long‐term stability of the whole system EBC‐base Si3N4 has to be subject of comprehensive future studies. Besides the superior high‐temperature properties, the whole application process from cost‐effective industrial production, reliability and failure probability, industrial handling up to specific conditions during the application have to be focused in order to bring advanced Si3N4 currently available to industrial application.